Incidence and Characterization of the Hypertensive Disorders during Pregnancy - María Pérez Hernández; Viviana Sáez Cantero; Gonzalo Aguero Alfonso; Hortensia González García; Antonio Alfonso Dávila; Felicia Vilches Luis (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: the incidence of hypertensive disorders during pregnancy varies from study to study. Nevertheless, it is generally associated with high maternal morbidity, mostly in cases of pre-eclampsia/eclampsia. Objective: to determine the incidence of hypertensive disorders during pregnancy and to characterize patients from a demographic and obstetric point of view. Method: a cross sectional, analytic and observational study was conducted from January 1st to December 31st, 2010, at the "Enrique Cabrera" General Teaching Hospital, including all patients diagnosed with some hypertensive disorder that gave birth at this hospital. The sample consisted on 108 patients. Data were processed using SPSS-11, 5 statistics program with determination of frequencies, percents, averages comparison and Chi square assessment. Results: the incidence of hypertensive disorders during pregnancy at the "Enrique Cabrera" Hospital during the year 2010 was of 4, 2 %, being chronic hypertension (16, 2 x 1000) the most common disorder. Predominating conditions were primiparity in patients with eclampsia (100 %), pre-eclampsia (75 %) and transitory hypertension (74, 6 %); cesarean and abruptio placentae in patients with pre-eclampsia/eclampsia and the admission at the intensive care of patients with eclampsia (75 %). Conclusion: although the incidence of serious hypertensive disorders during pregnancy was low, complications and surgical delivery in patients with pre-eclampsia /eclampsia were high.